The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/cncr.31049
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index at adolescence and risk of noncardia gastric cancer in a cohort of 1.79 million men and women

Abstract: The findings suggest that adolescent obesity, but not overweight, is associated with an increased risk for NCGC. Immigration from the FSU, a low residential SES, and a low education level are also significantly associated with the risk for NCGC. Cancer 2018;124:356-63. © 2017 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…15 In another study, obesity was significantly associated with the risk of noncardia gastric cancer. 15,16 In this study, BMI was significantly higher in re-ESD than surgery group (OR, 0.744; 95% CI, 0.563 to 0.983; p=0.037), which showed similar result with previous studies in that higher BMI was significantly associated with less aggressive histology of MGC.…”
Section: Discussionsupporting
confidence: 86%
“…15 In another study, obesity was significantly associated with the risk of noncardia gastric cancer. 15,16 In this study, BMI was significantly higher in re-ESD than surgery group (OR, 0.744; 95% CI, 0.563 to 0.983; p=0.037), which showed similar result with previous studies in that higher BMI was significantly associated with less aggressive histology of MGC.…”
Section: Discussionsupporting
confidence: 86%
“…Finally, our broad occupational category was not designed to detect occupational exposure and differed from occupational categories to detect specific occupational exposure . In addition, we could not assess multiple primary cancer cases or other possible risk factors (overweight, diet, institutional place‐based discrimination, physical activity, and cancer screening program) . Therefore, future studies are warranted to integrate all these aspects of cancer causal pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with atrophic gastritis might experience changes in appetite and dietary habits; therefore, given the cross-sectional design of our and others’ studies,20 40 we cannot rule out the possibility of reverse causation as an explanation for discrepant findings. A large prospective study among males in Israel showed that obesity at adolescence to be positively related to increased risk of non-cardia gastric cancer 41…”
Section: Discussionmentioning
confidence: 99%